Should antidiabetic treatment of type 2 diabetes in patients with heart failure differ from that in patients without? - Gitt, Anselm Kai (European journal of heart failure, 2012)
Aims Patients with type 2 diabetes are at high risk for developing heart failure. Evidence-based treatment recommendations with respect to the specific benefits or possible hazards of antidiabetic treatment are scarce. Methods and results In a systematic search we only identified randomized, controlled trials for thiazolidinediones. Further evidence is largely based on subgroup analyses of larger intervention studies in mostly systolic heart failure, on observational studies, or on registries. Acknowledging this lack of data, hyperglycaemia should be treated to appropriate guideline-recommended targets and hypoglycaemia avoided until this evidence becomes available. Thiazolidinediones should not be used because of an increased event rate in diabetic patients with established heart failure and a large increase in incident heart failure. All other glucose-lowering strategies might be used in patients with diabetes and heart failure, but specific precautions must be considered. Conclusions The documented lack of data calls for specific trials, as diabetes and heart failure as well as their co-morbidities are highly prevalent and are becoming even more important with an increasing prevalence of obesity and an ageing population.